Taras Shevchenko and The Cyril and Methodius Brotherhood - Сліпушко, Оксана Миколаївна (Київський національний університет імені Тараса Шевченка, 2026)
Background. The issue of Taras Shevchenko's connections with the Cyril and Methodius Brotherhood (Society) arises in two dimensions. First, no formal evidence of the poet's membership in the secret society has survived. Second, ideologically Shevchenko was close to the Brotherhood members, though distinguished by his radicalism and his own vision of Ukraine's development. His works created during his interaction with members of the Cyril and Methodius Society demonstrate anti-imperial, anti-colonial, and anti-serfdom motifs. They are imbued with democratic ideas of national freedom and personal liberty. Shevchenko and the Brotherhood members were united by common national ideals and a shared vision of the development of the Ukrainian people, their culture, and language within a European context, on equal terms with other nations and states. Methods. The study employs philological, comparative-historical, and textological methods. Results. Shevchenko's texts of this period are characterized by artistic historicism. He was neither the author nor even a co-author of the Society's program documents. However, his poetic works – such as the poems "The Dream" ("Everyone Has Their Own Fate…"), "The Caucasus", and the epistle "To the Dead, the Living, and the Unborn…" – are marked by pronounced radicalism and convey anti-autocratic and anti-imperial meanings. For the investigators, Shevchenko appeared to be the most dangerous figure because of the enormous influence of his ideas on society. The period of close ideological cooperation with the Cyril and Methodius Brotherhood (1846–1847) was marked by active poetic creativity filled with antiimperial, anti-autocratic sentiments and appeals for national and social liberation. The romantic symbolism of his youth was replaced by mature publicistic and sociopolitical theses. It was precisely during the so-called "Brotherhood period" that "The Dream", "The Caucasus", "To the Dead, the Living, and the Unborn…", "Kholodnyi Yar", and other satirical and accusatory poems were written. These works became the primary evidence of Shevchenko's guilt, rather than any possible participation in the Brotherhood. The poet openly criticizes autocracy, particularly the despotic tsar, the imperial machinery of violence and hypocrisy. He raises colonial issues, especially concerning Ukraine, the Caucasus, and other "borderlands" of the empire deprived of the right to freedom. The artist sharply criticizes the contemporary Ukrainian elite, especially the nobility, for historical oblivion, the loss of historical memory, and national identity. In fact, Shevchenko perceives himself as a prophet and judge, wielding the word as a weapon. Socio-political themes are accompanied by profound biblical allusions – prophecy, punishment, judgment. The artist skillfully combines high style with colloquial language. Conclusions. The poetic texts of T. Shevchenko were not merely ideologically close to the programmatic principles of the Cyril and Methodius Brotherhood – they inspired, directed, and shaped them. At the same time, Shevchenko's views were far more radical and revolutionary than the official documents of the Brotherhood, which determined the particular threat he posed to the imperial system. The Kobzar wrote revolutionary and effective texts – a kind of militant lyric poetry – that defined the essence and direction of political resistance and national struggle not only in his own time but also for future generations. Shevchenko's work powerfully actualized liberation ideas, placing national-state traditions at the forefront of socio-political life and defining the struggle for one's own spiritual statehood as paramount. These ideas formed the basis of his worldview.

Вступ. Питання зв'язків Тараса Шевченка з Кирило-Мефодіївським братством (товариством) постає у двох площинах. По-перше, не збереглося жодних формальних підтверджень участі поета у таємному товаристві. По-друге, світоглядно Шевченко був близьким із братчиками, відрізняючись своїм радикалізмом і власним баченням  розвитку України. Його творчість періоду взаємодії з учасниками Кирило-Мефодіївського товариства засвідчує мотиви антиімперіські, антиколоніальні, антикріпосницькі; перейнята демократичними ідеями свободи нації та особистості як її представника. Шевченка і братчиків єднали спільні національні ідеї, бачення розвитку українського народу, його культури і мови в європейському контексті, на рівних правах з іншими націями і державами.    Методи. У роботі використано методи дослідження: філологічний, порівняльно-історичний, текстологічний.   Результати. Для слідчих Шевченко виявився фігурою найбільш небезпечною через колосальний вплив його ідей на суспільство. Часи тісної ідейної співдії з Кирило-Мефодіївським братством у 1846-1847 рр. позначені активною творчістю поетичною, сповненою настроїв антиімперських, антисамодержавних, закликів до національного і соціального визволення. На зміну романтичній символіці юності приходять зрілі публіцистично-суспільні тези. Текстам Т. Шевченка цього періоду притаманний художній історизм. Саме у так званий "братський" період постали "Сон" ("У всякого своя доля…"), "Кавказ", "І мертвим, і живим, і ненарожденним…", "Холодний Яр" та інші сатирично-викривальні вірші, що і стали головними доказами вини Шевченка, а зовсім не можлива участь у Братстві. Поет відкрито критикує самодержавство, зокрема царя-деспота, імперську машину насильства і лицемірства. Він піднімає колоніальну проблематику, насамперед стосовно України, Кавказу, інших "окраїн" імперії, що поневолені, позбавлені права на свободу. Гостро критикує митець  і тогочасну українську еліту, зокрема панство за історичне забуття, втрату історичної пам'яті й національної ідентичності. Власне, Шевченко мислить себе пророком, суддею, в руках якого слово-зброя. Суспільно-політична проблематика супроводжується глибокими біблійними алюзіями, як пророцтво, покарання, суд. Митець талановито  поєднує високий стиль із розмовним. Висновки. Поетичні тексти Т. Шевченка не тільки ідейно близькі до програмних засад Кирило-Мефодіївського братства, а надихали їх, спрямовували і визначали. При цьому Шевченкові погляди значно радикальніші, революційніші, ніж офіційні документи братства, співавтором яких поет не був. Кобзар писав революційні, дієві тексти, своєрідну мілітарну лірику, що визначила суть і напрямки політичного опору і національної боротьби не тільки його часу, а і для нащадків. Шевченкова творчість з новою силою актуалізувала визвольні ідеї, поставивши на порядок денний суспільно-політичного життя національно-державницькі традиції, визначивши боротьбу за власну духовну державу як головну. Ці ідеї лягли в основу його світогляду. Загалом суспільно-політичний світогляд Т. Шевченка формувався під впливом багатьох чинників, одним із яких було Кирило-Мефодіївське братство. З його платформи митець узяв те, що найбільшою мірою імпонувало його поглядам, залишаючись незалежним у вираженні своїх переконань, виступаючи послідовним прихильником вільної Української Держави.
Тарас Шевченко і Кирило-Мефодіївське братство
Keywords: Taras Shevchenko; Cyril and Methodius Brotherhood; poetry; motif; creativity; message; historicism; artistic interpretation; Тарас Шевченко; Кирило-Мефодіївське братство; поезія; мотив; творчість; послання; історизм; художня інтерпретація